PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI 3 BATANGHARI - Amira Novalinda (Jurnal Edukasi dan Penelitian Matematika, 2021)
Student mathematics understanding ability is a basic ability who students need to have. It is will be better if the students can find the concept by themselves. By implementing problem based      learning, students can construct their knowledge and the relation of concept by solving the problems in real-life. So, it need to do the research in other to mathematics understanding ability to students is better than previous. This research is experiment0research by means0of nonequivalent posttest-only control group design. The0result of the research shows that problems based learning model can increase students’ mathematics understanding ability, students’ mathematics understanding ability with learning problem based learning0model0is better0than convensional learning model, so generally the development of     students’ understanding the mathematical concept of class VIII SMP Negeri 3 Batanghari has increased which can be seen from the score’s mean of1the final concept understanding test.Keywords – problem based learning model, students’ mathematics understanding ability